Errors in the administration of single-dose dry powder inhalers in patients with chronic bstructive pulmonary disease (COPD) - FARIA FURTADO CINTRA, RUI MIGUEL (2024)
Checking the effect of a therapeutic education program on the number of errors during the use of two single-dose dry powder inhalers in patients with chronic obstructive pulmonary disease and whether there are differences in the number and type of errors in inhalation technique after an education session, between the Aerolizer® and Handihaler® inhalers, validated using a specific checklist. The sample included 24 users, 17 men and 7 women, with an average age of 68 ± 11 years. It was found, for all the usual significance levels, that the education program contributed to a reduction in errors in administration procedures.